The impact of gut microbiota, inflammation and oxidative stress on endometriosis, pain, quality of life and condition of patients’ health - Anna Hanslik; Magdalena Mendak; Agata Białek; Monika Klimczak; Aleksandra Woskowska; Magdalena Domisiewicz (Quality in Sport, 2025)
Endometriosis is a chronic complex, systemic inflammatory disease which affects